Control-based consolidation : FRS 37 and its effect on the value relevance of consolidated financial statements in New Zealand : a thesis presented in partial fulfillment of the requirement for the Master of Business Studies (Accountancy) at Massey University, Albany, Auckland - Barcham, Rachael (Massey University, 2014)
Purpose: The purpose of this thesis is to determine whether the requirement for New Zealand organisations to switch from the ownership-based method of consolidation to the control-based method of consolidation increased the value relevance of consolidated financial statements in New Zealand. It takes advantage of the unique situation whereby all listed entities in New Zealand were required to comply with FRS 37: Consolidating Investments in Subsidiaries (FRS 37) in a year relatively free from changes to other financial standards. Motivation: The study was motivated by research undertaken by Hsu et al. (2012). Their research focused on the movement from the ownership-based method to the control-based method of consolidation of financial statements and whether this better reflected market value. They took advantage of the situation in Taiwan which similarly required all public firms to adopt Taiwan’s SFAS 7: Consolidated Financial Statements (TSFAS 7) at a set time. Research question: Did the change from the ownership-based method of consolidation under SSAP 8 to the control-based method of consolidation under FRS 37 increase the value relevance of consolidated financial statements in New Zealand? Sample selection and design: A sample of 54 entities listed on the New Zealand Stock Exchange (NZX) was used. The sample, although small, represented all of the final available population. Analysis of common accounting ratios was carried out and accounting variables affected by the switch to FRS 37 were analysed to determine changes in the value relevance of the consolidated financial statements. Findings: The adoption of FRS 37 led to an increase in value relevance of financial statements in New Zealand. However the ability to apply judgement to the application of control highlighted entities holding a larger number of subsidiaries and associates had a more complex structure than anticipated. Therefore holdings indirectly controlled may not have been captured with a lower instance of consolidation being achieved than was anticipated.
Keywords: Consolidated financial statements; Accounting standards, New Zealand; FRS 37; SSAP 8; Value relevance; Financial statements